Cause of wear-resistance enhancement of a polyurethane film composite by plasma-functionalized carbon nanotubes. (15th January 2019) - Ogawa, Daisuke; Michiya, Kazuki; Uchida, Hideo; Nakamura, Keiji
Abstract: Our previous investigation demonstrated that the wear-resistance of polyurethane (PU) film was enhanced by making the film composite utilize carbon nanotubes (CNTs). The use of plasma-treated CNTs further provides enhancement; this led to the hypothesis that the improvement could be more effective by applying isocyanate groups modified on CNTs treated with plasma. This was determined as the plasma contained nitrogen and oxygen species and because a material with isocyanate groups can function as a hardener of polyurethane. This article documents findings ensuant to our previous publication. Here, we present our investigation of the microscopic morphology of the PU film (physical aspect) and identified the chemical bonds (chemical aspect) in order to present the theorem of the enhancement. Observation of the morphology showed no specialty on the PU films with plasma-treated CNTs. On the other hand, an observation with an organic fluorescence, acridine yellow, showed evidence of the chemical aspect used to enhance the film composite with CNTs. Therefore, we concluded that the most effective method was to use isocyanate groups attached through plasma treatment, in order to improve PU wear-resistance.